Pengaruh Screentime Terhadap Gaya Hidup Sedentary Lifestyle Mahasiswa PG PAUD Unimed - Imel Lestari Zai; Adinda Tri Utami; Devi Kristina Tambunan; Wiwin Kristiani Waruwu; Tessalonika Br Tobing; Srinahyanti (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
A sedentary lifestyle, which is characterized by minimal physical activity and a predominance of passive activities, is increasingly becoming a concern, especially among students. This study aims to analyze the relationship between screen time and sedentary lifestyle in PGPAUD students at Medan State University. Using descriptive quantitative methods, data was collected through questionnaires from 85 respondents selected using purposive sampling techniques. The results of the analysis show that the relationship between screen time and a sedentary lifestyle is very weak, with a correlation of 0.119 and an R² value of 1.42%. This shows that screen time is not the main factor influencing students' sedentary lifestyle, but there are other factors that are more dominant. This finding is consistent with previous research which states that screen time is not always strongly correlated with sedentary behavior, but is more influenced by overall physical activity patterns. Therefore, a more comprehensive approach is needed to understand other factors that contribute to sedentary living habits among students